Pobídkový systém odměňování a informační neurčitost - Šnapka, Petr; Janečková, Viktorie (Univerzita Pardubice, 2011)
This paper aims to initiate an analytical account of the issues of economy condition applications incentive pay system employees. Economy and its fulfillment will be considered one of the conditions for effectiveness of the incentive application. The second condition for effectiveness will be achievement of the desired level of efficiency of application given incentive pay system. A sample can be considered a bonus pay system. Cost-effectiveness condition analysis is associated with an assessment of the impact of information uncertainty rules in structuring and quantifying the level of input factors (indicators) Determining the amount of potential incentives and performance of the condition of incentive pay.
Keywords: uncertainty of information; economy; incentive pay system; cost analysis; confidence interval; selection statistic sample; base statistic sample